5x(2x +1) = 0 --> x = - 0.5
25 - 100x^2 = 25*(1 - 4x^2) = 25*(1 - 2x)(1+2x) --> x 1 = +0.5 x2 = - 0.5
25x^2 - 14 = 0; 25x^2 = 14 ; x^2 = 0.56 --> x = v 0.56
2x^2 - 8 = 0; 2x^2 = 8; x^2 = 4; x1= 2; x2 = -2
4x^2 - 12=0; 4x^2 = 12; x^2 = 3 ; x = v 3
x^2 - 10x = 0 ; x(x - 10) = 0--> x = 10
4x^2 + 20x = 0; 4x(x + 5)=0--> x = - 5
2x^2 + x = 0; x(x + 1) = 0 --> x = - 1
3x^2 - 27 = 0; 3(x^2 - 9)=0; 3(x-3)(x+3)=0--> x1 = 3; x2 = - 3
4x^2 + 20x = 0; 4x(x + 5) = 0; x = - 5
2)(y - 3)(1 + b)
3) (m - 3)(3n + 5m)
4) ( c - d)(7a - 2b)
5) ( x + y)( a^2 + b^3)
6) ( a^2 + 2b^2)(x +y)
7) a(b - c) + c( b - c) = ( b - c)(a + c)
8) 2b( x - y) + ( x - y) = ( x - y)( 2b + 1)
9) 6(a - 2) - a( a - 2)= ( a - 2)(6 - a)
10) a^2( m - 2) - b( m - 2) = ( m - 2)(a^2 - b)
11) x( x - y) - y(x - y) - 3( x - y) = ( x - y)(x - y - 3)
12) a( b - 3) - ( b - 3) + b( b - 3) = ( b - 3)(a - 1 + b)
13) 5( a - b)( a - b) + (a - b)(a+ b) = (a - b)(5(a - b) + a + b) =
( a - b)(5a - 5b + a + b) = ( a - b)(6a - 4b)= 2(3a - 2b)(a - b)
14) a^3( 2 + a) + a^2(2 + a)^2 = (2 + a)(a^3 + a^2(2 + a)) = ( 2 +a)(a^3 + 2a^2 + a^3) = (2 + a)(2a^3 + 2a^2) = 2a^2(a + 1)(a + 2)